(untitled) (Research, Society and Development, 2021)
Brazilian fish farming is in expansion, with native species corresponding to 34.7% of its production. Catfish is one of the main farmed native species without intramuscular spines and are well accepted by the consumers. This review addresses the relationship between production and research of the main native catfish species in Brazil (Pseudoplatystoma and Rhamdia quelen) and also provides an overview of the main nutritional requirements studies with these species. It also aims to provide novel insights on nutrition research and species-specific formulations. Four main points were identified in this review: (i) surubim production is basically focused on hybrid fish, while many species have been investigated; (ii) benchmark diets in terms of nutritional composition and manufacturing technology such as extrusion or pelletization is necessary; (iii) tailored commercial diets for native species are scarce, especially when it comes to micronutrients, possibly impacting the industry with few commercial options and product lines; (iv) discrepancy between nutrition scientific research and the volume of commercial production of these species. Farming fish species with limited nutritional knowledge is possible, but it requires a common effort between the academy and the supply chain. The development of a scientific strategy in the area of nutrition aligned with the interests of the industry is essential for the expansion of the activity.